Kinetics of four limb joints during kick-start motion in competitive swimming - Sakai, S.; Koike, S.; Takeda, T.; Sengoku, Y.; Homma, M.; Takagi, H. (Sports Biomechanics, 2021)
The kick-start technique in competitive swimming generates a force acting on the starting platform owing to gravity, muscle contraction and resulting joint torque. To understand optimal body movement on the starting platform for maximising take-off velocity, it is necessary to investigate the joint torque in relation to the joint's rotation effects. Joint torques were calculated by inverse dynamics using kinetic and kinematic data. A one-way ANOVA showed significantly greater extensional torque for shoulders than for elbows or wrists, and for hips than for knees or ankles. The results indicated that the force of the hands was mainly influenced by extension torque at the shoulder joint. Hip joint extension torque on the front side lower limb (FSLL) was mainly used for supporting the body weight until hands off. After hands off, the front-foot force originated mainly by increases in ankle joint plantar flexion and knee joint extension torque on the FSLL. Rear side lower limb torque increases in the hip, knee and ankle joints provided the rear-foot force. This investigation clarified the magnitudes and functions of each joint torque acting on the extremities during the kick-start, providing practical information for improving starting performance.